Conflict Landscapes
1 online resource (xxxiv, 386 pages).
Keywords: Conflict Landscapes explores the long under-acknowledged and under-investigated aspects of where and how modern conflict landscapes interact and conjoin with pre-twentieth-century places, activities, and beliefs, as well as with individuals and groups. Investigating and understanding the often unpredictable power and legacies of landscapes that have seen (and often still viscerally embody) the consequences of mass death and destruction, the book shows, through these landscapes, the power of destruction to preserve, refocus, and often reconfigure the past. Responding to the complexity of modern conflict, the book offers a coherent, integrated, and sensitized hybrid approach, which calls on different disciplines where they overlap in a shared common terrain. Dealing with issues such as memory, identity, emotion, and wellbeing, the chapters tease out the human experience of modern conflict and its relationship to landscape. Conflict Landscapes will appeal to a wide range of disciplines involved in studying conflict, such as archaeology, anthropology, material culture studies, art history, cultural history, cultural geography, military history, and heritage and museum studies.